Persepsi Tokoh Ulama dan Adat Melayu Jambi Sekitar Kontroversi Penafsiran Kata Awliyâ’ dalam QS. Al-Ma’idah: 51 - Ahmad Syukri Saleh (Institut Agama Islam Negeri (IAIN) Curup, 2021)
The Perception of Jambi Malay Cleric and Traditional Leaders about the Controversy on the Interpretation of the Word Awliya' in QS. Al-Ma'idah: 51This article aims at uncovering the background behind controversy around Qur’anic interpretation of al-Ma’idah/5: 51 and how Muslim scholars and Malay traditional leaders of Jambi respond and view that issue. The interpretation on word awliyâ’ became viral in social media a few years ago, particularly when it related to prohibiton to elect public leader whose religion differed from his/her majority constituents. This research was conducted through qualitative method by using sociological approach in the frame of transformative Islam. Data were collected through observation, interview dan documentation. This research found that the controversy happened due to different interpretation and perception among Muslim scholars on the word awliyâ’. Such different interpretation and perception subsequently brought about a variety of responses and perpectives among Muslim scholars and traditional leaders of Jambi. Shortly, interpretation of a word in Qur’anic verse through textual and contextual method becomes a dominant trigger for the existence of such different interpretation and perception. Besides, a traditional root which is sociologically inherent in Malay community of Jambi takes part in determining attitude to which direction their tendencies on this controversy are